Going Your Own Way: A Cross-Cultural Validation of the Motivational Demands at Work Scale (Mind@Work) - Taris, Toon W.; Hu, Qiao (Frontiers in Psychology, 2020)
In modern jobs, performing well at work requires to an increasing degree that workers manage and motivate themselves for their tasks. Rather than to rely on a supervisor, they must set their own goals, decide how hard they work to achieve that goal, and decide when the task is completed. This manuscript describes the validation of an instrument that measures the extent to which workers must deal with such "motivational job demands"; the Motivational Demands at Work Scale (Mind@Work). Using data from a Dutch (N = 308) and a Chinese (N = 681) sample of working adults, confirmatory factor analysis showed that this instrument was reliable and robust in both samples, and that the factor structures obtained in both samples were highly comparable. Subsequent analyses demonstrated that high scores on the dimensions of the Mind@Work were associated with higher levels of engagement, work passion, job crafting and innovation behavior, even after controlling for job control and job demands. These findings suggest that motivational job demands can be measured in a reliable and valid way. Thus, more research that examines the potential of this new concept for well-being and performance of employees seems warranted.